Pemberian Ekstrak Etanol Purwoceng pada Masa Pascaplasentasi Meningkatkan Kinerja Reproduksi Tikus Bunting (SUPPLEMENTATION ETHANOLIC EXTRACT OF PIMPINELLA ALPINA AT POSTPLASENTATION ON PREGNANT RAT IMPROVE REPRODUCTIVE PERFORMANCE) - Satyaningtijas, Aryani Sismin; Maheshwari, Hera; Achmadi, Pudji; Bustaman, Isdoni; Kiranadi, Bambang; ., Julianto; Kurnia, Meta Levi (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
The study was carried out to observe the effect of ethanolic extract of estrogenic purwoceng given 13-21 days age of pregnancy on reproductive performance such as the weight of ovarium, uterus, placenta, andpups, correlation ratio of corpus luteum number, implantation site number, and litter size in rats. Thepregnant rats were divided in to two groups. One groups cosisted of rats treated with purwoceng (83.33 mg/kg body weight) and the other groups was used as control (no treatment). The ovary, uterus, placenta, andpups were collected and weighed on day 21 of pregnancy. The result showed that the rats given 83,33 mg/kg BW ethanol extract of purwoceng tended to increase the weight of ovarium, uterus, and pups but it didnot increase the weight of plasenta. Number of site of implantation, ratio of implantation site to numberof corpus luteum, and ratio of number of pups to implantation site were higher on rat given 83,33 mg/kgBW ethanol extract of purwoceng. Conclusion of this study is ethanol extract of Pimpinella alpina rootsgiven at postplasentation improve reproductive performance.
Keywords: purwoceng, ovarium, uterus, implantation, litter size